Effect of ozonation and UV irradiation on aflatoxin degradation of peanuts. Issue 4 (21st February 2019) - Li, Hui; Xiong, Zhongfei; Gui, Dali; Pan, Yanfang; Xu, Mengjun; Guo, Yanli; Leng, Juncai; Li, Xihong
Abstract: Aflatoxins (AFs) are secondary toxic metabolites. In this study, peanuts were contaminated with 500 µg/L B1, 250 µg/L B2, 250 µg/L G1, and 250 µg/L G2, then exposed to ultraviolet–ozone (UV/O3 ) with ozone concentrations of 3, 5, and 7 mg/L and exposure times of 10, 20, 30, and 60 min. With increasing exposure time and ozone concentration, the detoxification rates of AFB1, AFB2, AFG1, and AFG2 became more obvious, AFB1 showed the highest degradation rate. After peanuts were treated with 5 mg/L ozone under UV irradiation for 30 min, the degradation rates of AFB1 and AFs (AFs = AFB1 + AFB2 + AFG1 + AFG2 ) were 79.01% and 67.24%, respectively. Moisture content in peanuts decreased significantly ( p  < 0.05) with rising ozone concentration. No significances ( p  > 0.05) were found on the polyphenols, acid value, and peroxide value between UV/O3 ‐treated and non‐AF‐inoculated peanuts. UV/O3 was a promising method for AFs detoxification in peanuts without affecting nutritional quality. Practical applications: The main characteristic of peanut is its high nutritional value, such as vitamins, minerals, and fatty acids. Peanuts are contaminated by AFs easily. The effect of UV/O3 on the AFs, produced by Aspergillus flavus and Aspergillus parasiticus on peanuts, was determined. The results showed that UV/O3 was a promising method in degrading AFs, which was good for long‐term storage of peanuts.